2013
DOI: 10.2147/jpr.s43172
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the relationship between maternal fear of pain and children's conditioned pain modulation

Abstract: BackgroundParental behaviors, emotions, and cognitions are known to influence children’s response to pain. However, prior work has not tested the association between maternal psychological factors and children’s responses to a conditioned pain modulation (CPM) task. CPM refers to the reduction in perceived pain intensity for a test stimulus following application of a conditioning stimulus to a remote area of the body, and is thought to reflect the descending inhibition of nociceptive signals.MethodsThe present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…We can only speculate that parents may be more sensitive to the possible discomfort of the blood draw in girls than in boys; boys are often expected to be braver than girls. Another study found that girls' pain threshold is lower than that of boys, at least for slightly older children compared to the TEDDY children in our study [ 15 ]. This could indicate that the reaction of girls to the blood draw might be stronger than that of the boys and therefore the parents might be more prone to opt out when the child is a girl even when the child is younger.…”
Section: Discussionmentioning
confidence: 38%
“…We can only speculate that parents may be more sensitive to the possible discomfort of the blood draw in girls than in boys; boys are often expected to be braver than girls. Another study found that girls' pain threshold is lower than that of boys, at least for slightly older children compared to the TEDDY children in our study [ 15 ]. This could indicate that the reaction of girls to the blood draw might be stronger than that of the boys and therefore the parents might be more prone to opt out when the child is a girl even when the child is younger.…”
Section: Discussionmentioning
confidence: 38%
“…Consistent with previous research, PASS-20 scores were dichotomized via median split (e.g., Evans, Seidman, Lung, Zeltzer, & Tsao, 2013). The Kaplan Meier survival curve represents the probability of maintaining smoking abstinence for a given length of time while considering time in many small intervals (Kaplan & Meier, 1958).…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude of CPM was influenced by neither age nor maternal anxiety over pain in both boys and girls. Greater maternal pain anxiety was significantly associated with greater CPM anticipatory anxiety and pain-related fear in girls, but not in boys [24]. …”
Section: Conditioning and Learning Mechanismsmentioning
confidence: 99%